ISOLASI KUMARIN DARI KULIT BUAH LIMAU SUNDAI (Citrus nobilis Lour) - Melindra Mulia (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
Coumarin has been isolated and characteritated from rind of Citrus nobilis Lour by maseration methode with methanol. After fractionation by n-hexane and ethyl acetate, collected the phase ethyl acetate which positive of coumarin. From ethyl acetate extract coumarin have been isolated by column chromatography. The isolation results was obtain 2,159 g of pure white needle-shape crystalline with the melting point of 126,2-127,60C. Structure of the isolated coumarine was elucidated by spectroscopic methodes, UV-Vis,13C-NMR, 1H-NMR, 2D-NMR (DEPT/HSQC, COSY, NOESY, HMBC) and IR spectra. Based on the spectra data the isolated coumarine is marmin.